Probing Composite Vibrational Fingerprints in the Terahertz Range With Graphene Split Ring Resonator - Xinrong Mao; Yanfen Hang; Yuanguo Zhou; Jinfeng Zhu; Qiang Ren; Jianming Zhuo; Yijun Cai (IEEE Photonics Journal, 2020)
Sensors with single resonant mode often produce false positive when detecting the composite vibrational fingerprints of molecules in the terahertz (THz) range. In this study, a multi-resonant plasmonic structure, consisting of periodic graphene split ring resonator (SRR) arrays, is proposed for THz sensing. The effective detection of ultrathin (0.1 μm) lactose layer is given as an example to demonstrate the detection sensitivity. The vibrational fingerprints of lactose at 0.53 THz and 1.37 THz are enhanced in transmission spectra. Besides, resonant frequencies could be actively adjusted with the gate voltage applied on the SRR array. The physical mechanism of multi-resonance can be explained by a combination of LC resonance and dipole resonance of the structure, which can be observed in the electric field distributions. Moreover, the sensing performance can be further optimized by varying geometric parameters. Furthermore, the refractive index sensing performance of the sensor is also investigated by altering the surrounding medium on the surface. The designed sensor can work under an oblique incidence, which provides potential applications in biological analysis and medical diagnostics.